Respon Pertumbuhan dan Hasil Tanaman Jagung Manis terhadap Dosis Spora Endomikoriza Indigenus - MARHAENI PE, MARLIN; RAI, I NYOMAN; SUADA, I KETUT (Agrotrop : Journal on Agriculture Science, 2021)
Response of Growth and Yield of Sweet Corn to Dosage of Spores of Indigenous Endomycorrhizae. Endomycorrhizae is a form of mutualism association between fungi ( myces ) and roots ( rhiza ) of higher plants. The symbiotic relationship that occurs at the roots is mutually beneficial. Plants can provide carbon organic compounds for fungal growth, whereas fungi benefit plants by increasing nutrient uptake, water, producing enzymes, antibiotics and other compounds given to host plants. The study was conducted to know the effect of dosage of spores of endomycorrhizae indigenous to growth and yield of sweet corn. The experiments were carried out in laboratories and greenhouses. The design used was a completely randomized design with one factor namely the dose of spores of endomycorrhizae consisting of three levels, i.e. D 0 = without inoculation of endomycorrhizae, D 1 = 75 spores of endomycorrhizae/plant, and D 2 = 150 spores of endomycorrhizae/plants. The results showed that dose of spores of endomycorrhizae treatment had a significant effect on growth and yield of sweet corn. The highest fresh weight of cob was obtained at a dose of 150 spores/plant, namely 181.33 g / plant. Based on the results of this study, it is necessary to conduct research in the field using a dose of 150 spores of endomycorrhizae per plant.